“GIOCAMPUS” - An effective school-based intervention for breakfast promotion and overweight risk reduction - Vanelli, Maurizio; Monti, Giorgia; Volta, Elio; Finestrella, Viviana; Gkliati, Dimitra; Cangelosi, Marta; Caragnulo, Roberto; Vitale, Marco; Ingrosso, Lisa; Scazzina, Francesca (Acta Biomedica Atenei Parmensis, 2014)
The aim of this study was to evaluate the efficacy of a campaign promoting breakfast in primary school-children from the city of Parma, Italy, where 22 % of peer school-children had reported in 2005 to  skip breakfast. Two groups of children were interviewed by a multiple choice questionnaire on their breakfast habits. Group 1 counted only the children who  underwent the intensive campaign (n. 341), and  Group 2 a number of matched peers who did not attend any breakfast-promoting program (n. 291). Children who did not eat breakfast were found to be more numerous in Group 2 (17.5 %) than in  Group 1 (8.0 %; p=0.0001). In the Group 2 the percentage of  overweight (18.4 %) was higher compared to Group 1 patients (11.7 %; p=0.022). No significant difference in obesity percentage (8.9 vs 5.0 %; p=0.071).  Seventy five percent of children in Group I and the 25% of children in Group 2 (p=0.031) had one or two parents who had reported to skip routinely breakfast. Children with one or both parents used to skip breakfast had a greater odds ratio of 3.04  and  3 respectively of skipping breakfast compared to the children  with parents who had regularly  breakfast (p=0.0002). Compared to the children tested in 2005,  children admitted to   the Giocampus program showed: a significant decrease in breakfasting (22 vs 8 %; p=0.0001), a significant decrease in overweight (18.5 vs 11.7 %; p=0.003) but not in obesity (7.5 vs 5.0 %; p=0.138) status; a significant increase in consumption of cereals (p=0.0001) and fruit (p=0.0001). In conclusion, an intensive breakfast-centred strategy seems to be effective in breakfast promotion and in overweight risk decrease.